Revenue recognition in accounting theory and in accounting standards with applications in turkish practice - Karahan, Mehpare (My University, 2007)
MUHASEBE TEORİSİNDE VE MUHASEBE STANDARTLARINDA HASILATIN TANINMASI İLE TÜRKİYE UYGULAMALARININ UYARLANMASI Performansın ölçülmesi her büyüklükte şirket için önemlidir. Hasılat, şirketin içindeki veya dışındaki finansal bilgi kullanıcıları tarafından kullanılan performans ölçülerinden biridir. Bu sebepten dolayı hasılatın düzgün bir şekilde tanınması kritik bir işlemdir. Hasılatın tanınması iki çok önemli soruyu içerir: ne zaman hasılat tanınacak ve ne kadar hasılat tanınacak. Bu soruların cevapları şirketin iş yaptığı sektör ve finansal raporlamanın amacına göre değişir. International Accounting Standards Board ve Financial Accounting Standards Board’un hasılatın tanınması üzerine farklı iki grup standardı vardır. Fakat, hasılatın belirlenmesi konusuyla ilgili tek bir grup standart hazırlamayı amaçlayan bir proje üzerinde çalışmaktadırlar. UMS 18’in getirdiği yenilik satış tutarının makul değer ile ölçülmesidir. Dolayısıyla, faiz gelirinin satış hasılatından ayrılması ile ilgili bir uygulama yapılmıştır. UMS 18 ile uyumlu olarak, TMS de bu ayrıştırmayı istemektedir. Fakat, SPK düzenlemelerine uymak zorunda olan şirketler dışında uygulanmamaktadır. Bu uygulamanın yanında, hizmet hasılatıyla ile ilgili iki uygulama yapılmıştır. Güvenilir tahminde bulunabilmek hizmet hasılatı belirlenmesi için kritiktir. Bu iki uygulama, UMS 18’in hizmet sözleşmeleri uygulamalarının altın çizmektedir. Yapılan uygulamalardan birinde güvenilir tahminlerde bulunulabilinirken, diğer uygulamada güvenilir tahminlerde bulunulamamaktadır.

REVENUE RECOGNITION IN ACCOUNTING THEORY AND IN ACCOUTING STANDARDS WITH APPLICATIONS IN TURKISH PRACTICE Measuring performance is important for every size of companies. Revenue is one of the performance measures that are used by financial information users inside or outside the company. Because of this proper recognition of revenue is a critical process. Recognition of revenue includes two important questions: when revenue will be recognized and how much revenue will be recognized. Answers of these questions vary according to the sector that the company makes business or purpose of the financial reporting. International Accounting Standards Board and Financial Accounting Standards Board have different set of standards for revenue recognition. However, they are working on a project that aims to prepare a single set of standards that deals with the issue of revenue recognition. The innovation of IAS 18 on revenue recognition is the requirement of measurement of sales amount with fair value. Therefore an application is done for segregation of interest income from sales revenue. Parallel to IAS 18, TAS requires for this segregation. But it is not being implemented, except for those companies which are subject to CMB regulations. Beside, this application, two more applications are made for recognition of service revenue. Being able to make reliable estimates is critical for determining service revenue. These two applications underly the implementation of IAS 18 for service revenue. As in one of the applications reliable estimates can be made, in the other application reliable estimates cannot be made.
Keywords: Muhasebe; Muhasebe Standartları_Türkiye; Muhasebe Standatları